A case of granular cell ameloblastoma presenting as a non-healing socket. (2nd October 2019) - Ahmadi-Lari, Nazanin; Wilson, Mark; Hughes, Ceri; Thomas, Steven
Abstract : This case involves a 46-year-old female who was referred to the Bristol Dental Hospital Oral and Maxillofacial Surgery department with a non-healing socket. Investigations were carried out and biopsy confirmed diagnosis of granular cell ameloblastoma. She was subsequently treated with a segmental resection and a bone graft to reconstruct the defect of her mandible. CPD/Clinical Relevance: This report highlights the significance of taking a full history and carrying out a thorough clinical examination to ensure significant diagnoses are not missed.